EXTRACTION AND PARTIAL PURIFICATION OF LIPOPOLYSACCHARIDE FROM KLEBSIELLA OXYTOCA AND STUDY OF ITS ROLE IN THE PATHOGENICITY - Majeed, Raghad; Flayyih, May (Iraqi Journal of Science, 2024)
K.oxytoca bacteria was isolated from patients with urinary tract infection[UTI]from both sexes and at different ages and were identified by biochemical tests.the isolates were sensive to Amikicin Nitrofurantion and Ticarcillin \Clavulinic acidand resistant to β-lactam antibiotics The isolate that gave highest percentage ofresistant to antibiotics was used for LPS extraction by phenol-hot water method.LPS partial purification by gel filtration on Sepharose Cl-6B-200 showed that thepercentage of carbohydrate in the partially purified LPS was 26.6% and percentageof binding protein was 0.06% and no nucleic acid was found. The LD50 of thebacteria and LPS was determined by injection of the male mice, it was 3.16X 106 cfufor bacteria and 266 μg/ml for LPS.